POLYGENIC RISK SCORE SEBAGAI PREDIKTOR DIABETES MELLITUS TIPE 2: SYSTEMATIC RIVIEW - Ni Ketut Diah Ayu Pramisswari; Ety Apriliana; Selvi Marcellia; Putu Ristyaning Ayu Sangging (Yayasan Nusantara Hasana Berdikari, 2026)
Type 2 diabetes mellitus (T2DM) is a multifactorial metabolic disease with a significant genetic contribution. Polygenic risk score (PRS) has been developed to integrate the cumulative effects of multiple genetic variants to improve T2DM risk prediction. This Systematic review aimed to evaluate the role of PRS in predicting T2DM incidence, disease progression, and related complications across different populations. This study was conducted in accordance with the PRISMA guidelines, with a literature search performed using the PubMed database and keywords related to PRS and T2DM. Included studies were observational in design and assessed the association between PRS and T2DM incidence or clinical outcomes. Three main studies with case-control, cross-sectional, and cohort designs were analyzed. The results demonstrated that PRS was significantly associated with increased T2DM risk, disease progression, and metabolic complications such as liver fibrosis, including in the context of organ transplantation. Integration of PRS with traditional clinical risk factors improved predictive performance. PRS has the potential to support precision-based T2DM risk stratification, although further cross-population validation is still required.